The Venezuelan Migration Crisis and Its Economic Impact on Colombia's Labor Market - Kůsová, Johana; Šváb, Patrik; Agustina, Shirley Basauli; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor’s thesis examines the effects of Venezuelan migration on the Colombian labor market, focusing on the period from 2014 to 2023. The theoretical part describes the economic and political crisis in Venezuela, the socio-economic context of Colombia, and a review of existing research on the topic. The second part of the thesis focuses on the scale and demographic structure of Venezuelan migration to Colombia – particularly the geographic distribution, age, gender, and education levels of migrants. The third, analytical part addresses the impact of migration on unemployment, informal employment, and wage developments across different sectors. The analysis is based on secondary data from Colombia’s national statistics office DANE, the World Bank, and the International Labour Organization (ILO), and is complemented by insights from academic literature.
Vedoucí práce: Patrik Šváb
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses